Erotic Narration of Syair Lebai Guntur - Mustari Mustari (Hasanuddin University, 2018)
The text of Syair Lebay Guntur contained in the Syair Lebay Guntur text by Raja Ali Haji records the traces of the 'disgraceful' behavior of some Malay people in the past who practiced